INTENSI KEWIRAUSAHAAN MAHASISWA: STUDI PERBANDINGAN ANTARA INDONESIA, JEPANG DAN NORWEGIA - Nurul Indarti; Rokhima Rostiani (Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
Survey towards 332 students from three different universities in three different countries (Indonesia, Japan and Norway) shows that entrepreneurial intentions among the students and the influencing factors differs across countries. The main objective is to compare the impact of different economic and cultural contexts. Results reveals that self-efficacy influence entrepreneurial intention among Indonesian and Norwegian students. Instrumental readiness and working experience become key factors that influence entrepreneurial intention among Norwegian students. Educational background becomes a key factor that influence entrepreneurial intention among Indonesian students, in the opposite direction. Need for achievement, age and gender have no statistically significant impact. However, they only explain 28.2 percent, 14.2 percent, and 24.8 percent (R2) of the total variance of the entrepreneurial intention for Indonesia, Japan and Norway respectively. This study is expected to be inputs for universities, government institutions, and policy makers so that can stimulate and encourage entrepreneurship spirit.